RURAL TOURISM OF EASTERN SERBIA – HUMAN RESOURCES MANAGEMENT AND MOTIVATION - Ilić, Biljana; Đukić, Gordana P.; Nikolić, Miloš (Economics of Agriculture, 2022)
Depending on the existence and dominance of a resource in a certain rural area, different forms of rural tourism can be developed. Human resources are the most important factor in all forms of tourism business, including rural tourism. The subject of this paper is a survey of employee satisfaction in rural tourism, in Eastern Serbia - in the villages of the Timok region. The authors aimed to highlight the most important motivating factors of employees in smaller rural households. The technique of survey questionnaires was applied, while the obtained data were processed by the appropriate statistical method. The paper represents a modest contribution to the research of human resources motivation in the field of rural tourism, but the results obtained by the research can be recommendations to the general managers of rural households, in which way to best motivate their employees.